Virus-induced Systemic Vasculitides: New Therapeutic Approaches - Loïc Guillevin (Clinical and Developmental Immunology)
The best therapeutic strategy in virus-induced vasculitides should take into account the etiology of the disease and be adapted to the pathogenesis. The combination of antiviral treatments and plasma exchanges has been proven effective in polyarteritis nodosa (PAN). In human immunodeficiency virus (HIV)-related vasculitis this strategy is also effective and does not jeopardize, like cytotoxic agents, the outcome of AIDS. In vasculitis related to HCV-associated cryoglobulinemia, plasma exchanges improve the outcome but the poor effectiveness of antiviral drugs is not able to favor, usually, a definite recovery of the patients and relapses are frequent.